9 - Staple Crops Processing Zones, Food Security and Restoration of Local Food Systems in Zimbabwe - Hazvinei Vhumbunu, Clayton (Africa Development, 2022)
With the adoption of Staple Crops Processing Zones (SCPZs) and Agro- Processing Zones (APZs) by Western countries and Asia, it is time for Zimbabwe to follow suit in order to address food insecurity challenges that the country has been facing since the year 2000. This article examines the possibility, rationality, utility, practicality and mechanics of designing and implementing SCPZs in Zimbabwe’s identified agro-processing nodes in order to boost and integrate food productivity, processing and marketing whilst restoring local food systems. Methodologically, the study utilises secondary data sources, drawing comparisons and valuable lessons from cases of successful SCPZs implementation in Europe, China and Asia. The agricultural development theory provides the theoretical framework that anchors the study, whilst the SCPZs as well as the food security rural-urban migration nexus constitute the conceptual frames of analysis. The research findings suggest that although there are multiple threats to food security in Zimbabwe, the adoption and implementation of SCPZs equally present significant opportunities for boosting food security and restoring local food systems through value chain developments. The study findings are key in informing the format, structure, design and operational modalities of SCPZs as a strategy for boosting food security and restoring local food systems in Zimbabwe.